A Retrospective Study on the Safety and Efficacy of Leflunomide in Dogs. (21st August 2017) - Sato, M.; Veir, J.K.; Legare, M.; Lappin, M.R.
Abstract : Background: Little clinical information is available concerning the use of leflunomide in dogs with immune‐mediated diseases. Objectives: To report the safety and efficacy of leflunomide for the treatment of naturally occurring immune‐mediated diseases in dogs. Animals: Ninety‐two dogs treated with leflunomide for management of suspected immune‐mediated diseases. Methods: Retrospective medical record review from Jan 1995 to Dec 2014. Data that were extracted from the medical records included signalment, body weight, underlying indication for leflunomide, dosage of leflunomide, treatment duration, concurrent medications, treatment response, and adverse events. Results: Adverse events that could be related to leflunomide administration included diarrhea (3 of 92, 3.3%), lethargy (2 of 92, 2.2%), unexplained hemorrhage (3 of 92, 3.3%), thrombocytopenia (2 of 31, 6.5%), and increased liver enzyme activities (1 of 16, 6.3%). Significant dose differences between dogs with adverse events (n = 11; median, 2.9 mg/kg/d; range, 1.8–3.6 mg/kg/d) and dogs without adverse events (n = 81; median, 1.6 mg/kg/d; range, 0.8–4.3 mg/kg/d) were found ( P < 0.001). Treatment response could be evaluated in 17 dogs. Of these 17 dogs, 12 dogs (70.5%) had an apparent positive response to the use of leflunomide. There was no significant difference ( P = 0.22) in dosages between dogs that responded to leflunomide (n = 12; median, 1.9 mg/kg/d; range, 1.0–3.5 mg/kg/d) and those that did not respond (n = 5; median, 1.7 mg/kg/d; range, 1.0–2.0 mg/kg/d). Conclusions and Clinical Importance: Results suggest that the starting dosage of leflunomide should be 2 mg/kg/d rather than the currently suggested dosage of 3–4 mg/kg/d.